Air pollution and short‐term clinical outcomes of patients with acute myocardial infarction. (June 2017) - Lee, Min Woo; Choi, Byoung Geol; Kim, Suhng Wook; Rha, Seung‐Woon; Shim, Min Suk; Kim, Dae Jin; Seo, Hong Seog; Oh, Dong Joo; Jeong, Myung ho; ,
Summary: Ambient air pollution is well‐known to be a serious risk factor for cardiovascular diseases, stroke, and death. However, the association between air pollutants (AP) exposure and short‐term clinical outcomes in acute myocardial infarction (AMI) patients (pts) has not been elucidated well. In the present study, 37 880 AMI pts were enrolled from October 2005 to December 2013 in a nationwide large‐scale, prospective, multicentre Korea AMI registry (KAMIR registry;http://www.kamir.or.kr ). We obtained data on AP (e.g., NO2, SO2, CO, O3 and PM10 ) from the Korean National Institute of Environmental Research (NIER;http://www.nier.go.kr ). Clinical endpoints included death, recurrent myocardial infarction (Re‐MI), any revascularization and composite of all‐cause death and Re‐MI. Exposure to AP is defined as the average exposure to AP within 24 hours before AMI admission. We observed that a 0.01 part per million (ppm) increase in NO2 concentration, 0.001 ppm increase in SO2 concentration, and 0.1 ppm increase in CO concentration each increased the risk of total death by 9.7% (95% CI, 6.2%‐13.4%), 1.9% (95% CI, 0.3%‐3.6%), and 2.1% (95% CI, 0.5%‐3.9%), respectively. Exceptionally, O3 decreased the risk of total death by 0.6% (95% CI −0.2% to −1.0%) per 0.01 ppm increase. PM10 was not related to any cardiovascular events. AP were each stratified into five quintiles according to ranges of AP levels. After adjusting analysis for risk variables, only high quintiles (Q4, Q5) of NO2 were positively associated with total death, cardiac death and MI, while SO2, CO, O3 and PM10 were shown to be not related to any cardiovascular events at all levels. In AMI patients, each AP and its concentration has shown a different effect to short‐term mortality and cardiovascular events.